PEMBERDAYAAN WANITA DI DESA SEDAYU MAGELANG MELALUI KETRAMPILAN MEMPRODUKSI VIRGIN COCONUT OIL (VCO) - Murni Yuniwati (LPPM IST AKPRIND Yogyakarta, 2018)
Most women in the Sedayu area Magelang, especially in rural areas, are generally housewives who do not earn. Actually women have considerable potential to help household economies that can improve the economy of the village. The women's empowerment program can be done by increasing skills, among others by producing materials needed by the community, for example the skills to produce Virgin Coconut Oil (VCO). VCO is pure coconut oil which is needed by the pharmaceutical industry, cosmetics industry and the general public who use it directly for health purposes. Pure coconut oil with the main content of lauric acid and capric acid is very beneficial for the health of the body. Many researchers have proven that lauric acid in the human body will be converted into monolaurin which can overcome various viral attacks such as HIV, herpes, influenza and various pathogenic bacteria. The economic value of VCO on the market is quite high. The raw material needed to produce VCO is coconut meat which is very easy to obtain at a fairly cheap price. The manufacturing process can be done easily and the equipment used is also very simple. With these skills, it is expected that women in Sedayu hamlet can get substantial profits that can improve the economy of their households in particular, and the village economy in general.